Peran Teknologi dalam Meningkatkan Pola Komunikasi dan Dampaknya terhadap Kinerja Pegawai di Kantor Desa Cikole - Maulida Sifa Yusnita; Regita Gusrianisa (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The development of information and communication technology has significantly transformed governance systems, including at the village level. Cikole Village in West Bandung Regency serves as an interesting case as it integrates communication technology into its daily operations. This study aims to identify the role of technology in enhancing communication patterns among employees and its impact on their performance. A qualitative descriptive approach was used, with data collected through direct observation and in-depth interviews with the Village Secretary of Cikole. The findings reveal that the use of applications such as WhatsApp, Telegram, Line, Google Drive, and online meeting platforms like Zoom and Google Meet has improved communication efficiency, accelerated decision-making processes, and strengthened internal coordination. Technology also supports public service transparency through the Village Information System (SID) and the Village Financial System (Siskeudes). However, challenges such as limited internet access and technical server issues still persist. This study recommends improving network infrastructure and providing continuous training for village officials to optimize technology use. The results are expected to serve as a reference for other villages in utilizing communication technology to enhance performance and public service quality. Keywords: Communication, Performance, Service, Technology, Village Governance